A new freshwater goby of Rhinogobius Gill, 1859 (Teleostei, Gobiidae) from South Central Vietnam - Chen, I-Shiung; Nguyen, Anh-Tuan; Huynh, Quang-Thien (Zootaxa, 2024)
A new species of freshwater gobiid fish of genus Rhinogobius Gill, 1859, was collected from the Cai Phan Rang River basin, South Central Vietnam. Rhinogobius phuocbinhensis n. sp. can be well distinguished from other congeners by its specific patterns of coloration and meristic features: (1) fins rays: second dorsal fin rays I/8; anal fin rays I/8; pectoral fin rays modally 19; (2) squamation: longitudinal scale series 26–27 (modally 27); perdorsal scales 9–11 (modally 9); vertebral count 26; and (3) specific colouration pattern: densely-set of small blackish brown spots on cheek and interorbital region to snout in male and many small blackish brown dots in first dorsal fin of both sexes. A brief morphological comparison of this new species with related species would be also addressed.